Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025908
|View full text |Cite
|
Sign up to set email alerts
|

Designing Cultural Values into Interaction

Abstract: In this paper, we highlight possibilities for designing intangible cultural values into interactions with technologies in heritage spaces. We do this specifically through the design of ʔeləw ̓ k ̓ ʷ -Belongings, an interactive tangible table installed in a cultural heritage museum. The tabletop was collaboratively designed to communicate complex and narrative information and values about Musqueam culture. Rather than focusing only on content and interface design, we wanted visitors to also experience Musqueam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 47 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Later the core of this has been transformed from the still preservation of cultural heritage into the interdependent inheritance within the economic system [19,20]. Some studies have shown the scholarly understandings of TCPs has been transformed into a more dynamic and intertemporal vitality of cultural value [21,22]. TCPs are regarded as living resources to inform the cultural and economic development in the current context; it has been exploited to nourish product design to improve users' cultural satisfaction, especially for the young generation [18,23].…”
Section: Cultural Product Design and Consumers' Attitudementioning
confidence: 99%
“…Later the core of this has been transformed from the still preservation of cultural heritage into the interdependent inheritance within the economic system [19,20]. Some studies have shown the scholarly understandings of TCPs has been transformed into a more dynamic and intertemporal vitality of cultural value [21,22]. TCPs are regarded as living resources to inform the cultural and economic development in the current context; it has been exploited to nourish product design to improve users' cultural satisfaction, especially for the young generation [18,23].…”
Section: Cultural Product Design and Consumers' Attitudementioning
confidence: 99%
“…Similarly, as a means for connecting historical or complex concepts to visitors' current knowledge, designers often use more familiar symbols within their exhibits. For instance, designers may choose to use a Coca-Cola can to represent global trade within an exhibit on historical trade routes (Muntean et al, 2017). The familiarity of symbols facilitates visitors' comparisons and associations with prior knowledge, providing parents and children with a jumping off point for abstraction.…”
Section: Evidence-based Solutionmentioning
confidence: 99%
“…Within the HCI and design literature, gifting tends to either emerge as a finding [30,33,39], serve as a metaphor or framework [9,27,44,49,55], or stand as the topic being directly addressed [46,53]. Some of this work discusses the importance of effort in conveying meaning, including Odom et al's observation of teenagers adding notes and images to playlists [39, p. 1496] and Muntean et al's use of effort to explain differing cultural values [38].…”
Section: Gifting Experiencesmentioning
confidence: 99%